2023
DOI: 10.1002/mco2.203
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia signaling in cancer: Implications for therapeutic interventions

Abstract: Hypoxia is a persistent physiological feature of many different solid tumors and a key driver of malignancy, and in recent years, it has been recognized as an important target for cancer therapy. Hypoxia occurs in the majority of solid tumors due to a poor vascular oxygen supply that is not sufficient to meet the needs of rapidly proliferating cancer cells. A hypoxic tumor microenvironment (TME) can reduce the effectiveness of other tumor therapies, such as radiotherapy, chemotherapy, and immunotherapy. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 480 publications
(923 reference statements)
1
22
0
Order By: Relevance
“…Such minor decrease suggested that although Ab-PEGylation provided desirable shield for removing nonspecific binding, its affinity to CD147 Ag also decreased slightly. This result is consistent with previous observations, 18,48 and site-specific PEGylation may be considered in the future. Two limitations exist in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Such minor decrease suggested that although Ab-PEGylation provided desirable shield for removing nonspecific binding, its affinity to CD147 Ag also decreased slightly. This result is consistent with previous observations, 18,48 and site-specific PEGylation may be considered in the future. Two limitations exist in this study.…”
Section: Discussionsupporting
confidence: 93%
“…These microenvironmental features are distinct from those of normal tissues and can trigger specific chemical reactions. Hypoxic tumor microenvironment has been exploited to design stimuli‐responsive prodrugs or nanodrugs 15–18 . Hypoxic cells produce 100–1000 times more nitroreductase than normoxic cells, which can reduce azobenzene (azo)‐containing drugs for conditional release 19–21 .…”
Section: Introductionmentioning
confidence: 99%
“…In the hypoxic tumor microenvironment, HIF-1α is activated through the mTOR (mammalian target of rapamycin), NF-κB (nuclear factor kappa B), and JAK (Janus kinase)-STAT signaling pathways by receptors on the plasma membrane (e.g., TCR-T cell receptor, GFR-growth factor receptor, IL-6R and TLR-Toll-like receptor) [ 71 ]. Upregulated HIF-1α combines with HIF-1β to form a dimer in the nucleus.…”
Section: Metabolic Pathways and Signaling Activated In Tnbcmentioning
confidence: 99%
“…Identifying it promptly allows targeted therapies to address hypoxia-related aggressiveness, potentially curbing tumour progression and bettering patient outcomes. 7 While various methods detect tumour hypoxia, each bears limitations. Polarographic oxygen electrodes, the gold standard for accuracy, remain invasive and impractical for clinical use.…”
mentioning
confidence: 99%
“…Early detection of hypoxia in cancer is pivotal, guiding tailored treatments for enhanced efficacy. Identifying it promptly allows targeted therapies to address hypoxia‐related aggressiveness, potentially curbing tumour progression and bettering patient outcomes 7 . While various methods detect tumour hypoxia, each bears limitations.…”
mentioning
confidence: 99%